Regulation of Growth of the Mother Cell and Chromosome Replication during Sporulation of Bacillus subtilis - Xenopoulos, Panagiotis (American Society for Microbiology, 2011)
During spore formation, Bacillus subtilis divides asymmetrically, resulting in two cells with different fates. Immediately after division, the transcription factor σ(F) becomes active in the smaller prespore, followed by activation of σ(E) in the larger mother cell. We recently showed that a delay in σ(E) activation resulted in the novel phenotype of two spores (twins) forming within the same mother cell. Mother cells bearing twins are substantially longer than mother cells with single spores. Here we explore the regulation of the growth and DNA replication of the mother cell. We find that length correlates with chromosome number in the mother cell. We show that replication and growth could occur after asymmetric division in mother cells with no active σ(E). In contrast, when σ(E) was active, replication and growth ceased. In growing mother cells, with no active σ(E), Spo0A-directed transcription levels remained low. In the presence of active σ(E), Spo0A-directed gene expression was enhanced in the mother cells. Artificial Spo0A activation blocked mother cell growth in the absence of σ(E). Spo0A activation blocked growth even in the absence of SirA, the Spo0A-directed inhibitor of the initiation of replication. Together, the results indicate that the burst of Spo0A-directed expression along with the activation of σ(E) provides mechanisms to block the DNA replication and growth of the mother cell.